2020
DOI: 10.3126/nmcj.v22i3.32656
|View full text |Cite
|
Sign up to set email alerts
|

Health Seeking Behavior and Cost of Care of Chronic Dermatophytosis: A Hospital-Based Cross-Sectional Study

Abstract: Recent trend in onslaught of chronic and recurrent dermatophytosis not amenable to conventional dose and duration of antifungal agents has been observed in Nepal and India. The major factor implicated behind this surge is use of over-the-counter fixed drug combination containing topical steroids. This study aimed to examine the health seeking behavior, pattern of drug use and cost of care of chronic dermatophytosis in Nepalese population. Ninety-one patients with the diagnosis of chronic dermatophytosis of ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Similar findings were reported in a study conducted by Joshi et al in which the majority of the patients belonged to 19 years to 28 years age group (41.6%). 10 Different types of tinea infections were diagnosed in the patients. Amongst these tinea corporis and cruris were responsible for maximum infections (52.7%) whereas tinea faciei, capitis, pedis, versicolor, manuum and incognito were observed comparatively less in our study population and similar results were observed in a study done by Dutta et al 11 Superficial fungal infection can be a chronic condition due to recurrences as was seen in 74 (29.4%) patients who had history of similar infections in past.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in a study conducted by Joshi et al in which the majority of the patients belonged to 19 years to 28 years age group (41.6%). 10 Different types of tinea infections were diagnosed in the patients. Amongst these tinea corporis and cruris were responsible for maximum infections (52.7%) whereas tinea faciei, capitis, pedis, versicolor, manuum and incognito were observed comparatively less in our study population and similar results were observed in a study done by Dutta et al 11 Superficial fungal infection can be a chronic condition due to recurrences as was seen in 74 (29.4%) patients who had history of similar infections in past.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar dos tratamentos disponíveis, o surgimento de novos casos e de recorrência dessa infecção se tornou um problema de saúde pública (Nweze & Eke, 2018;Pereira et al, 2020;Rengasamy et al, 2020). Estudos apontam aumento na incidência de casos de dermatofitose crônica e recorrentes sem resposta ao tratamento pelos antifúngicos, como fluconazol e terbinafina (Dogra & Uprety, 2016;Joshi et al, 2020).…”
Section: Introductionunclassified
“…This has been highlighted by studies where majority of patients do not visit dermatologist and purchase medication from local pharmacy. 6 Hence knowledge, attitude, practice surveys are essential to help plan, implement and evaluate patient behaviour. It can identify knowledge gaps, cultural beliefs, or behavioural patterns so that it can facilitate understanding and action.…”
mentioning
confidence: 99%